First fossil occurrence of the genus platychelyna hayward and thorpe (Bryozoa: Cheilostomata) - López Gappa, Juan José; Pérez, Leandro Martín; Griffin, Miguel (Ameghiniana)
Platychelyna secunda sp. nov. is described based on material collected in the Monte León Formation, Patagonia, Argentina (early Miocene). This is the second species of Platychelyna Hayward and Thorpe to be described and the first fossil representative, expanding the stratigraphic range of the genus by ~20 Ma. P. secunda and P. planulata Hayward show similar geographic distributions in the southern tip of South America. Zooid size is ~50% larger in the recent species compared to the fossil one, which could be related to the cooling of the water masses in the Southwest Atlantic since the opening of the Drake Passage towards the end of the Oligocene. Fil: López Gappa, Juan José. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Pérez, Leandro Martín. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina Fil: Griffin, Miguel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina